1,3-Dibenzyl-6-bromo-1H-imidazo[4,5-b]pyridin-2(3H)-one - Dahmani, S.; Rodi, Y.K.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The imidazopyridine fused-ring in the title compound, C(20)H(16)BrN(3)O, is planar (r.m.s. deviation = 0.011 angstrom). The phenyl rings of the benzyl substitutents twist away from the central five-membered ring in opposite directions; the rings are aligned at 61.3 (1) and 71.2 (1)degrees with respect to this ring.